The Role of Optimism, Innovativeness, Discomfort, and Insecurity in the Acceptance of Bank Jago’s Mobile Application: A TRI–TAM Approach - Rehatta, Stanny Dewanty; Hardini, Inkreswari Retno; Berutu, Meta Bara (CV. Civiliza Publishing, 2025)
The development of digital banks in Indonesia, such as Bank Jago, has transformed the way people access financial services. The success of adopting these services is influenced not only by technology availability but also by users' psychological readiness. This study combines TRI and TAM to analyze how innovativeness, optimism, insecurity, and discomfort affect PEOU, PU, and ITU among Indonesia's digital generation. The research uses a quantitative survey and PLS-SEM analysis. Results indicate that optimism significantly boosts PEOU but does not significantly affect PU or ITU. Innovativeness significantly enhances PU and PEOU but does not influence ITU. Contrary to expectations, discomfort demonstrates a significant positive relationship with PU but has no notable impact on PEOU or ITU. Insecurity shows no significant effect on any variables. Moreover, PEOU significantly increases PU but negatively influences ITU, PU does not significantly impact ITU. These findings suggest that ease of use and PU are not always the main factors driving the intention to adopt technology, particularly among users familiar with digital tools. This research contributes to the literature on TRI and TAM integration and offers practical insights for digital financial service developers to consider psychological readiness when designing technology adoption strategies.